Letter - Longuet, Jean
021-0062-001 CONSEIL GENERAL DE LA SEINE REPUBLIQUE FRANCAISE LIBERTE EGALITE FRATERNITE 10th April 1937. Mr TEWSON, Trade Union Congress, TRANSPORT HOUSE, LONDON. Dear Comrade, On the 4th of March last, I sent you my photo for an article, whioh was supposed to appear in the Herald or some other labour paper, on the International Conference in London, having been asked to do so by the International Trade's Union Federation in Paris; but no article appeared and my photo was not used. I suppose there has been some misunderstanding. At any rate, will you, please, let me have my photo, which I need. Faithfully yours, Jean Longuet 292/946/21/62